Towards a theory of international production of infrastructure services - Turolla, Frederico Araujo (Internext, 2013)
This paper discusses elements of a theory of international production of infrastructure services. I present a microeconomic view on the major market failures of the infrastructure sectors, and argue that the idiosyncrasies of these sectors may require modification of current dominant international business theories as applied in the explanation of the specific context of infrastructure foreign direct investments. The paper discusses the relevant ownership advantages, mostly in standard setting and capitalization; location advantages that are clearer, but do not play in the conventional fashion. Preemptive entry will secure first mover advantages in light of the transient nature of the windows of opportunity. Internalization, although apparently not relevant, may take place in specific transactions involving procurement of projects and financing. The process of internationalization of infrastructure firms may also merit adaptations, even considering the more recent version of the Uppsala model which considers liability of outsidership.